2014
DOI: 10.1371/journal.pone.0108714
|View full text |Cite|
|
Sign up to set email alerts
|

Mycobiome of the Bat White Nose Syndrome Affected Caves and Mines Reveals Diversity of Fungi and Local Adaptation by the Fungal Pathogen Pseudogymnoascus (Geomyces) destructans

Abstract: Current investigations of bat White Nose Syndrome (WNS) and the causative fungus Pseudogymnoascus (Geomyces) destructans (Pd) are intensely focused on the reasons for the appearance of the disease in the Northeast and its rapid spread in the US and Canada. Urgent steps are still needed for the mitigation or control of Pd to save bats. We hypothesized that a focus on fungal community would advance the understanding of ecology and ecosystem processes that are crucial in the disease transmission cycle. This study… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
36
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 67 publications
2
36
0
Order By: Relevance
“…We swabbed cave walls more than 1 m from roosting bats, if any were present, and obtained results with DPYA that generally match or exceed those obtained with culture-independent methods, while also allowing us to confirm the viability of Pd. Our yield of Pd from wall swabs using SAB is similar to Lorch et al (2013) and Zhang et al (2014).…”
Section: Discussionsupporting
confidence: 61%
See 3 more Smart Citations
“…We swabbed cave walls more than 1 m from roosting bats, if any were present, and obtained results with DPYA that generally match or exceed those obtained with culture-independent methods, while also allowing us to confirm the viability of Pd. Our yield of Pd from wall swabs using SAB is similar to Lorch et al (2013) and Zhang et al (2014).…”
Section: Discussionsupporting
confidence: 61%
“…These inconsistencies may reflect differences in the detection of Pd DNA using cultureindependent approaches compared to culture-dependent methods, which reveal only viable spores, or possibly site differences. Lorch et al (2013) and Zhang et al (2014) found that the probability of detecting Pd was higher using molecular methods compared to culture techniques. Viable Pd was cultured from only 13.8 % (n ¼ 195) of soil samples in Pdpositive hibernacula using SAB (Lorch et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Sampling of individual hosts to monitor such potential spread is often not feasible (particularly in the cases of migratory birds, mammals, and insects), but eDNA analyses of fecal material has much potential as a host-independent and non-invasive method of parasite monitoring; for example, helminths in rat feces [66], fungal community characteristics associated with the spread of Bat White Nose Syndrome [67], Blastocystis in dog feces [68], and Cryptosporidium species in cattle feces [69]. Hitch-hiking is a particular concern with micro-eukaryotic parasites, which are at least in some cases more easily dispersed than larger metazoans [70,71] and more difficult to find and/or identify in pathology screens of hosts.…”
Section: Edna Facilitates Indirect Detection Of Both Parasites and Hostsmentioning
confidence: 99%